1993
DOI: 10.1161/01.hyp.22.5.677
|View full text |Cite
|
Sign up to set email alerts
|

ATP-sensitive potassium channels in the basilar artery during chronic hypertension.

Abstract: We examined the hypothesis that dilatation of the basilar artery in response to activation of ATP-sensitive potassium channels is impaired in stroke-prone spontaneously hypertensive rats (SHRSP). Changes in basilar artery diameter in response to aprikalim, a direct activator of ATP-sensitive potassium channels, were measured in anesthetized SHRSP and normotensive Wistar-Kyoto (WKY) rats through a cranial window. Topical application of aprikalim increased basilar artery diameter in WKY rats. Glibenclamide, a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…44 Also, dilation of pial arteries in response to RP52891, a K ATP channel activator, was observed to be impaired in diabetic rats, 45 whereas basilar artery dilation in response to aprikalim was blunted in stroke-prone spontaneously hypertensive rats. 46 Because K ϩ channels regulate the tone of cerebral blood vessels, 7 impaired vascular responsiveness to activators of these channels after brain injury suggests the contribution of such signal transduction mechanisms to stroke pathogenesis. It is presently uncertain, however, whether the observations made in the present study can be translated to the adult state or if they are unique to the perinate.…”
Section: Discussionmentioning
confidence: 99%
“…44 Also, dilation of pial arteries in response to RP52891, a K ATP channel activator, was observed to be impaired in diabetic rats, 45 whereas basilar artery dilation in response to aprikalim was blunted in stroke-prone spontaneously hypertensive rats. 46 Because K ϩ channels regulate the tone of cerebral blood vessels, 7 impaired vascular responsiveness to activators of these channels after brain injury suggests the contribution of such signal transduction mechanisms to stroke pathogenesis. It is presently uncertain, however, whether the observations made in the present study can be translated to the adult state or if they are unique to the perinate.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed and inward-rectifying K ϩ channels have been postulated to contribute to the regulation of cerebrovascular tone, and glibenclamide-sensitive K ϩ channels also may modulate cerebrovascular excitability under some conditions. [39][40][41][42][43][44][45] To date, however, early studies in the SHR vasculature have not documented an enhanced K ϩ current through other types of K ϩ channels, which are insensitive to Ca 2ϩ activation. Rather, Martens and Gelband 11 have recently reported a reduced density of delayed-rectifier K ϩ current in renal arteries of SHR, and Kitazono et al 45 observed an impaired vasodilator function of glibenclamide-sensitive K ϩ channels in basilar arteries of stroke-prone SHR.…”
Section: Pressure-induced Upregulation May Be Specific To the K Ca Chmentioning
confidence: 99%
“…2 Moreover, there is increasing evidence that K ϩ channel function may be variously altered in several disease states that predispose to stroke. 6 For example, cerebral vasorelaxation in response to openers of ATP-sensitive K ϩ channels is impaired during chronic hypertension, 7 diabetes, 8,9 atherosclerosis, 10 and after ischemia 11 or brain injury 12 but may be augmented after subarachnoid hemorrhage (SAH). [13][14][15] In addition, the function of inwardly rectifying K ϩ channels is impaired after ischemia and reper-…”
mentioning
confidence: 99%